2012
DOI: 10.1038/ijos.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors correlated with the success rate of miniscrews in orthodontic treatment

Abstract: Miniscrews offer a reliable alternative for anchorage during orthodontic treatment, particularly for non-cooperative patients or periodontal patients with alveolar bone loss. The study aims at assessing the correlation of various clinical indicators with the success or failure of miniscrews used for anchorage during orthodontic treatment. Thirty-four consecutive patients with a cumulative total of 82 miniscrews implanted participated in the study. Generalized Estimating Equations were used to assess the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…The area between the upper first premolar and second premolar in the maxilla and mandible showed a higher success rates, whereas the area between the first molar and second molar in the maxilla and mandible had the lowest success rate. These findings were similar to those found in other research …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The area between the upper first premolar and second premolar in the maxilla and mandible showed a higher success rates, whereas the area between the first molar and second molar in the maxilla and mandible had the lowest success rate. These findings were similar to those found in other research …”
Section: Discussionsupporting
confidence: 93%
“…Watanabe et al. and Lai and Chen also concluded that the success rate was higher if placed in the attached gingiva than movable mucosa …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study reported that the number of miniscrews used per patient is correlated with miniscrew failure rate. 37 Further studies are needed to draw a more definitive conclusion.…”
Section: Discussionmentioning
confidence: 96%